Independent formation of longitudinal forces in bent beams - Kobielak, Sylwester; Troszczynski, Grzegorz (Communications - Scientific letters of the University of Zilina, 2000)
This paper deals with the phenomenon of horizontal constraints being strutted by bent beams. This phenomenon takes place when rotating ends of beam sections encounter the resistance of horizontal constraints. Consequently, reactions occur between the constraints and the beam horizontal which induce a longitudinal compression force. Equations for two load cases: a uniformly distributed and concentrated force applied to the span centre, allowing to determine the value of this force and its influence on deflection and load capacity on the on the basis of the linear and non-linear theory were derived. The analysis carried out on this base showed an advantageous effect of the discussed phenomenon on the beam behaviour. It was proved that as horizontal supports stiffness increases the deflection decreases considerably and its strength increases. An especially significant increase in the load capacity was observed in the case of materials with low tensile strength and high compression strength.